1994
DOI: 10.1017/s0952523800001565
|View full text |Cite
|
Sign up to set email alerts
|

Constant light affects retinal dopamine levels and blocks deprivation myopia but not lens-induced refractive errors in chickens

Abstract: Chickens were raised with either translucent occluders or lenses, both under normal light cycles (12–h light/12–h dark) and in constant light (CL). Under normal light cycles, eyes with occluders became very myopic, and eyes with lenses became either relatively hyperopic (positive lenses) or myopic (negative lenses). After the treatment, retinal dopamine (DA), DOPAC, and serotonin levels were measured by high-pressure liquid chromatography (HPLC-EC). A significant drop in daytime retinal DOPAC (-20%) was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 21 publications
5
81
0
Order By: Relevance
“…These studies have been confirmed using guinea pigs (Dong et al, 2011a) in form-deprivation myopia, reductions in both dopamine and its metabolites were observed. Other studies observing chickens also showed similar results (Bartmann et al, 1994;Megaw et al, 2006;Stone et al, 1989b).…”
Section: Dopamine and Dopamine Receptorssupporting
confidence: 74%
See 3 more Smart Citations
“…These studies have been confirmed using guinea pigs (Dong et al, 2011a) in form-deprivation myopia, reductions in both dopamine and its metabolites were observed. Other studies observing chickens also showed similar results (Bartmann et al, 1994;Megaw et al, 2006;Stone et al, 1989b).…”
Section: Dopamine and Dopamine Receptorssupporting
confidence: 74%
“…FDM in chickens could be suppressed by constant light (Bartmann et al, 1994) and a similar inhibitory effect on myopia has been demonstrated in rhesus monkeys exposed to high intensity of light (range between 18000 and 28000 Lux) (Smith et al, 2012a). However, Lauber (1987) raised that constant light could induce glaucoma in the chicks about three decades earlier.…”
Section: Animal Studies On Light Levels and Myopiamentioning
confidence: 60%
See 2 more Smart Citations
“…The use of modified translucent occluders demonstrates that retinal dopamine levels inversely correlate with the degree of axial elongation (Stone, Pendrak et al 2006). Retinal dopamine levels exhibit a bidirectional response to retinal blur in chicks, with lens-induced myopia decreasing and hyperopia increasing the levels respectively (Guo, Sivak et al 1995) although this effect is not universally reported (Bartmann, Schaeffel et al 1994). The increase in retinal dopamine associated with the slowing of axial growth in lens-induced hyperopia parallels recovery from form-deprivation myopia in the chick where a similar relationship between dopamine level and axial growth is reported (Pendrak, Nguyen et al 1997).…”
Section: Dopamine Melatonin and Refractive Development 61 Dopaminementioning
confidence: 99%